2017
DOI: 10.1080/07420528.2017.1280046
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors contributed to circannual rhythm of semen quality

Abstract: We investigated whether human semen parameters present circannual rhythm or not, and whether environmental factors exert on semen quality. This retrospective study used data of patients mainly from Reproductive Medicine Center and Urology and Andrology Clinic of a general hospital in China. Sperm concentration and motility were measured by computer aided sperm analysis (CASA). Sperm morphology was scored based on the strict criteria (WHO, 2010). The Kruskal-Wallis rank test was used to investigate the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Normal sperm morphology was evaluated in samples stained using the Papanicolaou technique (Baso Diagnostics Inc., Zhuhai, China) and analyzed according to the WHO 2010 criteria. 20…”
Section: Semen Analysismentioning
confidence: 99%
“…Normal sperm morphology was evaluated in samples stained using the Papanicolaou technique (Baso Diagnostics Inc., Zhuhai, China) and analyzed according to the WHO 2010 criteria. 20…”
Section: Semen Analysismentioning
confidence: 99%
“…The circumpolar populations are exposed by the unique complex of adverse environmental factors such as low air temperature, marked seasonality, and peculiar photoperiod with very low day-light hours in winter and elevated ones in summer. These adverse conditions, especially contrast photoperiod, can vastly affect male fertility since the spermatogenesis is known to be susceptible to environmental factors including a length of light day [50,51]. It was revealed that the circumpolar populations are characterized by elevated basal metabolic rate [52]; hyperactivity of the thyroid gland, increased fatty acid metabolism [53], with both functional and genetic factors contributing to metabolic adaptation to the northern conditions [52].…”
Section: Discussionmentioning
confidence: 99%
“…A study of 12,245 semen samples from 7068 males showed that semen quality (total sperm count, sperm motility or normal morphology) varied according to both circadian and circannual rhythms in humans (Xie et al 2018). Increased length of daylight positively correlated with progressive sperm motility as well (Mao et al 2017). Genetic epidemiological studies have also shown that circadian clock gene polymorphisms are linked to semen parameters and risk for infertility.…”
Section: The Role Of Circadian System In Male Reproductive Biologymentioning
confidence: 99%
“…Hodzic et al (2013) Patients with idiopathic infertility (n = 517) and fertile men (n = 444)Genetic variability in CLOCK associated with male infertilityMao et al (2017) Cases for routine semen analysis (n = 8168), morphology ( n = 5819) and anti-sperm antibodies analysis (n = 5544)Positive correlation between increased length of daylight and progressive sperm motilityXie et al (2018) 12,245 semen samples (n = 7068 men) Circadian and circannual variations on semen qualityNi et al (2019) Human semen samples (n = 10,752) Diurnal variations on sperm DNA fragmentation Chronobiology, reproduction and offspring healthR85Reproduction (2020) 160 R79-R94…”
mentioning
confidence: 99%